Pengaruh Tax Planning, Prudence Accounting dan Company Growth terhadap Firm Value dengan ESG Performance sebagai Pemoderasi Pada Perusahaan FMCG di BEI - Limajatini, Limajatini; Tambun, Sihar; Natapunta, Riyandi (Universitas 17 Agustus 1945 Jakarta, 2025)
This study aims to examine the effect of tax planning, prudence accounting, and company growth on firm value, and to analyze ESG Performance as a moderating variable. The study was conducted on Fast Moving Consumer Goods (FMCG) sector companies listed on the Indonesia Stock Exchange for the period 2020–2023. The research method used is quantitative with a causal approach. Data analysis was carried out using Stata with a moderation regression test through the Moderated Regression Analysis approach. The results of the study prove that tax planning and company growth have a positive impact on firm value. While prudence accounting has no effect on firm value. ESG performance is proven to weaken the effect of prudence accounting on firm value. Then ESG performance is unable to moderate the effect of tax planning and company growth on firm performance.